A case of drug‐induced hypersensitivity syndrome due to diaminodiphenyl sulfone complicated by acute respiratory failure with atypical erythema around existing prurigo. Issue 2 (18th March 2020) - Akaji, Kazuya; Arase, Noriko; Nakagawa, Yukinobu; Tanemura, Atsushi; Katayama, Ichiro; Fujimoto, Manabu
Abstract : We report a case of drug‐induced hypersensitivity syndrome (DIHS) due to diaminodiphenyl sulfone (dapsone) complicated by acute respiratory failure. Erythema only expanded from his preexisting prurigo. The proportion of regulatory T cells in the skin was relatively low, and overall steroid reactivity was favorable.